The Difficulty Analysis of Students Spatial Ability Based on Level Van Hiele in Problem Based Learning - Chairunnisa Chairunnisa; Edy Surya; Bornok Sinaga (BIRCU, 2021)
This study aims to (1) determine the level of students' spatial ability at Van Hiele's level in problem-based learning. (2) to find out the location of the students' difficulties in solving spatial power problems with the Van Hiele level. This research is a qualitative descriptive study. The subjects of this study were students of class XII SMK Bima Utomo Batang Kuis. The object of this research is the spatial ability based on Van Hiele's level in Problem Based Learning. The results of this study indicate that the level of spatial ability in the low category reaches 51.4%, while the medium category reaches 34.3%, and the high category reaches 14.3%. Subjects in the low category experienced skill difficultiesSubject S.01 (low spatial ability), at Level 1 experienced skill difficulties (question number 1) and concept difficulty (question number 4), at Level 2 experienced skill difficulties, at Level 3 and Level 4 experienced difficulty in principle. Subject S.02 (low spatial ability), has difficulty skills at Level 2 and has difficulty in principle at Level 3 and Level 4. Subject S.03 (moderate spatial ability), has difficulty in principle at Level 3 and Level 4. Subject S. 04 (moderate spatial ability), has difficulty skills at Level 3 and has difficulty in principle at Level 4. Subject S.05 (high spatial ability), has difficulty in principle at Level 4. Subject S.06 (high spatial ability), has difficulty principles at Level 4.Based on the results of this study, it is expected to be an inspiration for users.